(untitled) (Research, Society and Development, 2024)
Colorectal cancer has been the cause of death in men and women before the age of 50. It is known that tumor development is influenced by several factors, such as obesity, diabetes, physical inactivity and bad eating habits. The present study aimed to analyze the daily habits of patients with colorectal cancer in a local hospital. The study was longitudinal and descriptive with participants diagnosed between 2019 and 2023 with tumors in the colon and rectum that were not derived from metastasis. Using questionnaires, based on the "Food Guide: how to have a Healthy Diet" from the Ministry of Health (Brazil), adding questions about practicing physical activity. The data on weight and height was extracted from medical records, and Body Mass Index (BMI) divided patients into two groups: control group (BMI between 18.6 kg/m2 and 24.9 kg/m2) and overweight/obese (BMI ≥ 25 kg/m2). The data were arranged as relative and absolute frequencies and analyzed using the GraphPad Prism® 8 program using the chi-square (χ2) statistical test with a minimum acceptable significance level of p < 0.05. According to the results, it was noted that most participants need to pay attention to their eating habits according to the instrument score and daily physical activity and that a very small portion have a considerably healthy lifestyle.